The Implementation of Authentic Assessment in Course Syllabus Incorporating the Pragmatic Acquisition - Setiyo Wahyuni, Elli; Arieffiani, Deasy (Universitas PGRI Adi Buana Surabaya, 2021)
The fact that students have lack of reading comprehension as the result of ineffective implementation in course syllabus. The study aims at implementing authentic assessment in extensive reading. The objective of activities in authentic assessment is to enhance the students’ pragmatic acquisition in understanding political news text. Qualitative method design is used by conducting classroom action research. The finding indicates that the pedagogy implementation provides various tasks in improving the students’ pragmatic acquisition. The result reveals that reading strategy can be reinforced through listening, writing, and speaking to have an understanding in a context. Forty-five students in extensive reading class answer open-ended questionnaire and the result shows that pragmatic acquisition is an effective strategy to comprehend the reading text. The integration of authentic assessment and the acquisition of semantic meaning are suggested to be investigated in future research.